2006
DOI: 10.1158/0008-5472.can-06-2761
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Inactivation of the HOXA Gene Cluster in Breast Cancer

Abstract: Using an integrated approach of epigenomic scanning and gene expression profiling, we found aberrant methylation and epigenetic silencing of a small neighborhood of contiguous genes-the HOXA gene cluster in human breast cancer. The observed transcriptional repression was localized to f100 kb of the HOXA gene cluster and did not extend to genes located upstream or downstream of the cluster. Bisulfite sequencing, chromatin immunoprecipitation, and quantitative reverse transcription-PCR analysis confirmed that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 20 publications
4
113
1
1
Order By: Relevance
“…coexpressed genes ͉ nuclear lamina P revious studies by others and us have shown that many coexpressed tissue-specific genes are organized in large continuous clusters on chromosomes of diverse species (1)(2)(3), and similar clustering has been observed for the genes deregulated in diverse diseases (4)(5)(6)(7)(8). These findings imply that higherorder chromatin structure may be involved in regulation of extensive multigenic regions in both normal development and its pathological disruptions.…”
mentioning
confidence: 62%
“…coexpressed genes ͉ nuclear lamina P revious studies by others and us have shown that many coexpressed tissue-specific genes are organized in large continuous clusters on chromosomes of diverse species (1)(2)(3), and similar clustering has been observed for the genes deregulated in diverse diseases (4)(5)(6)(7)(8). These findings imply that higherorder chromatin structure may be involved in regulation of extensive multigenic regions in both normal development and its pathological disruptions.…”
mentioning
confidence: 62%
“…The HOXA5 promoter region was methylated in 16 of 20 p53-negative breast tumor specimens (29). While this manuscript was in preparation, methylation of the HOXA gene cluster in breast cancer was reported (30)…”
Section: Discussionmentioning
confidence: 93%
“…In phase I of our two-phase strategy to characterize epigenetic phenomena in DLBCL, we measured DNA methylation levels in seven ABC-DLBCL and seven GCB-DLBCL tumors using CpG island microarray assays 12,16,17 (Figure 1). This provided a rapid means of evaluating the methylation-dependent cleavage of 442 unique gene-associated CpG islands by McrBC endonuclease (Supplementary Table 1 and Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%